Analisis Peranan Unsur Pimpinan Dalam Pengembangan Budaya Organisasi - Sylvie Agustina (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2018)
This article is the result of research on the topic of Organizational Culture Development through the Role of Leaders in the North Indralaya District of Ogan Ilir Regency. The research was conducted by combining efforts in the form of roles carried out by the leadership towards the development of organizational culture. There are six dimensions of organizational culture that are examined by taking reference to the theory of organizational culture. The research was conducted with a descriptive qualitative method approach. The main informants of the research were the elements of leadership in the North Indralaya District of Ogan Ilir Regency. Data analysis was carried out with interactive methods from Miles and Hubberman. Triangulation is done by comparing various sources to check the validity of the research answers. The results of the research concluded that the leadership elements of the North Indralaya District of Ogan Ilir Regency were actively involved and played a role through various efforts in maintaining and developing six dimensions of organizational culture in accordance with the theoretical references used. The condition of organizational culture in the Indralaya North District Office in the qualitative context has also been running well. There are three influential supporting factors in developing a good and effective organizational culture in the Government of North Indralaya District. In addition to supporting factors there is also one inhibiting factor in the development of organizational culture in the Government of North Indralaya District.